Between Tone And Stress In Hamar - Petrollino, Sara (My University, 2019)
This paper provides a preliminary description of the word-prosodic system of Hamar, a South Omotic language spoken in South West Ethiopia. The prosodic system of Hamar shows properties of both stress accent and tone: accent is lexically contrastive in nouns, but not in verbs, where it has a grammatical function. Post-lexical tonal oppositions arise when lexical accent and grammatical accent interact in both nouns and verbs. The prosodic behaviour of Hamar nouns and verbs is in line with the pattern proposed by Smith (2011), whereby nouns are higher than verbs in a hierarchy of phonological privilege.
Keywords: Hamar; tone; stress; Ethiopia